Short- and Long-Term Repeated Forced Swim Stress Induce Depressive-Like Phenotype in Mice: Effectiveness of 3-[(4-Chlorophenyl)Selanyl]-1-Methyl-1H-Indole - Pesarico, Ana Paula; Birmann, Paloma T.; Pinto, Rodrigo; Padilha, Nathalia Batista; Lenardão, Eder João; Savegnago, Lucielli (Frontiers in Behavioral Neuroscience, 2020)
Exposure to stress highly correlates with the emergence of mood-related illnesses. Therefore, the present study was designed to characterize the acute and chronic effects of 3-((4-chlorophenyl)selanyl)-1-methyl-1H-indole (CMI) on depressive-like behavior induced by repeated forced swim stress (FSS) in male adult Swiss mice. In the repeated FSS, mice were placed in water to swim for a single trial during a 15-min period. Twenty-four hours after the first FSS, the animals were placed in water to swim through a series of four trials, and each of them swam for 6 min long; between each trial, mice were towel dried and returned to their home cage for 6 min. In addition, the oxidative stress in the prefrontal cortex and hippocampus and corticosterone levels of plasma of mice were investigated. The animals exposed to FSS were treated with CM in two different protocols. In protocol 1, CMI [1 and 10 mg/kg, intragastric (i.g.) route] or fluoxetine, a positive control (10 mg/kg, i.g. route), were administered 30 min before of sections of repeated FSS in both days of stress. After the last section of repeated FSS, the mice performed first the spontaneous locomotor activity and after the tail suspension test. In protocol 2, CMI or fluoxetine (1 mg/kg, i.g. route) was administered for 20 days after the exposition of repeated FSS. The spontaneous locomotor activity, tail suspension, and forced swimming tests were performed in this order after 24 h of last administration of CMI or fluoxetine. The euthanasia of animals was performed after the behavioral tests. CMI and fluoxetine abolished the depressive-like behavior induced by repeated FSS in mice in the two different treatments. CMI modulated the oxidative stress in the prefrontal cortices and hippocampi of mice subjected to repeated FSS. Mice subjected to repeated FSS had an increase in the corticosterone levels and CMI regulated the levels of this glucocorticoid. These findings demonstrate that CMI was effective to abolish the depressive-like behavior induced by repeated FSS, which was accompanied by changes in the corticosterone levels and oxidative stress of prefrontal cortices and hippocampi of mice.